Optimizing Social Studies Learning through Implementation Improvements to the Merdeka Curriculum - Muhammad Ardiansyah; Elvira Ria Tirtana (Journal of Smart Pedagogy and Education, 2025)
This study investigates the optimization of Social Studies (IPS) learning through the implementation of Indonesia's Merdeka Curriculum. While aiming to enhance student-centered learning, its implementation faces significant obstacles, including gaps in teachers' conceptual understanding, infrastructural limitations, and difficulties in integrating character values. Employing a qualitative approach with a case study design, this research gathered data through in-depth interviews, participant observation, and document analysis to comprehensively analyze these obstacles, their causal factors, and potential improvement strategies. Key findings reveal that learning ineffectiveness stems from a combination of structural factors (e.g., uneven policy socialization), pedagogical factors (e.g., dominance of conventional methods), and contextual factors (e.g., student heterogeneity). Consequently, this research formulates an integrated optimization strategy that encompasses differentiated learning, transformative integration of Pancasila values, and sustained teacher capacity building through professional learning communities. This holistic strategy is shown to significantly improve student engagement, conceptual understanding, and character value internalization, underscoring its importance for effective curriculum reform.